Eusyllinae and “Incertae sedis” syllids (Annelida: Syllidae) from South America, with a new species from Brazil and a new combination for a Peruvian species - Fukuda, Marcelo V.; Nogueira, João M. M.; Martín, Guillermo San (Zootaxa, 2015)
We herein present the first taxonomic account on the genera Amblyosyllis, Brevicirrosyllis, Eusyllis and Opisthodonta from Brazilian waters, with the description of Eusyllis nonatoi sp. nov. The new species is characterized by having transverse dark stripes on dorsum, unidentate, relatively short falciger blades with inverted dorso-ventral gradation in length, and distally rounded to inconspicuously bifid dorsal simple chaetae. In adittion, the description of Eusyllis liniata comb. nov., from Peru, originally described as belonging to Odontosyllis, is also provided. Finally, we amend the description of Opisthodonta russelli, originally described from anterior fragments only.